Do older adults attempt suicide for attention? - Gutierrez, Denise Machado Duran; Minayo, Maria Cecília de Souza; Sousa, Amandia Braga Lima; Grubits, Sonia (Saúde e Sociedade, 2020)
This study analyzes part of the results of a multicentric national research that investigated suicidal ideation and suicide attempts in older adults. The text aims to question the so-called “attention seeking” behavior, used by health professionals and families of older patients when referring to their motivation for self-destructive behavior. This qualitative research used semistructured interviews to thoroughly understand this phenomenon. We analyzed 12 cases of older adults with suicidal ideation and/or suicide attempts and reports from four professionals who expressed their opinion on the “attention seeking” behavior attributed to these patients. The data collected underwent dialectical hermeneutic analysis. The research focused on factors associated with situations faced by older adults, aiming to relate the feelings of those who idealized or tried to commit suicide and the “attention seeking” behavior. As a result, two major analytical categories emerged: attention seeking according to older adults; and attention seeking according to health professionals. The study showed that the connection family members or health professionals establish between “attention seeking” and intent to commit suicide is, in general, very tenuous; rather, it characterizes a proper manifestation that something is unwell in the older adult’s life. We found a predominance of common-sense understandings about these facts that have no direct relationship with the desire or intention of self-inflicted death, but represent a difficulty in understanding feelings of isolation and loneliness.